Cuproptosis: molecular mechanisms, cancer prognosis, and therapeutic applications - Yating Cong; Na Li; Zixin Zhang; Yan Shang; Hailong Zhao (Journal of Translational Medicine)
Abstract Cuproptosis differs from other forms of cell death, such as apoptosis, necroptosis, and ferroptosis, in its unique molecular mechanisms and signaling pathways. In this review, we delve into the cellular metabolic pathways of copper, highlighting the role of copper in biomolecule synthesis, mitochondrial respiration, and antioxidant defense. Furthermore, we elucidate the relationship between cuproptosis-related genes (CRGs) and cancer prognosis, analyzing their expression patterns across various tumor types and their impact on patient outcomes. Our review also uncovers the potential therapeutic applications of copper chelators, copper ionophores, and copper-based nanomaterials in oncology. In addition, we discuss the emerging role of cuproptosis in remodeling the tumor microenvironment, enhancing immune cell infiltration, and converting “cold tumors” into “hot tumors” that respond better to immunotherapy. In short, this review underscores the pivotal importance of cuproptosis in cancer biology and highlights its translational potential as a novel therapeutic target.